Research on Oxygenation Components under a High-Pressure Oxygen Environment - Haowen Yang; Dongsheng Jiang (Applied Sciences, 2023)
Oxygen nozzles play an important role in aircraft oxygen systems, and the oxygen valve is one of the most important components of the oxygen nozzle. In order to investigate the ignition source of three fires of a certain type of aircraft, combustion analysis, energy spectrum analysis, and material analysis were conducted. Based on the results of the analysis, oxygen impact tests were carried out under different conditions to identify the superior material and to calculate the lifetime of a PA1010 oxygen valve. The test platform was constructed at the National Key Experimental Base of Fire Science. The PA1010 oxygen nozzle and the F3 oxygen nozzle were the main test subjects. The test results show that the lifetime of the PA1010 oxygen valve under high-pressure oxygen was about 2532, and F3 was the safer material for the oxygen valve. This research provides a reference for the safety design of oxygen valves under high-pressure environments and facilitates further research into aircraft oxygen systems.